Design of a MW-scale thermo-chemical energy storage reactor. (November 2018) - Angerer, Michael; Becker, Moritz; Härzschel, Stefan; Kröper, Konstantin; Gleis, Stephan; Vandersickel, Annelies; Spliethoff, Hartmut
Abstract: The reversible exothermic reaction of CaO with water is considered one of the most promising reactions for high temperature thermal energy storage. In this paper, a novel technical design of a MW-scale thermochemical energy storage reactor for this reaction is presented. The aim is to provide an easy, modular and scalable reactor, suitable for industrial scale application. The reactor concept features a bubbling fluidized bed with a continuous, guided solid flow and immersed heat exchanger tubes. To investigate the reactor design, a model is build using clustered CSTRs. The technical feasibility of the concept is proven in experimental tests, which are also used to identify key parameters of the model. Fluidization of the fine CaO/Ca(OH)2 powder was found to be challenging, but problems were overcome using mild calcination conditions and a special gas distributor plate. Using the model, it is found, that a thermal power of 15 MW can be expected from a reactor volume of 100 m 3 . To study influences of different parameters on the reactor model performance, a sensitivity analysis is carried out and heat transfer between the reactor and the immersed heat exchangers is found to have by far the largest influence and the reaction system performance. Future research should therefore focus more on heat transfer. Highlights: A novel design for a MW-scale fluidized bed thermochemical storage is developed. Proof of concept is achieved by experimental pretests. A model of the reactor design is build using clustered CSTRs. A power output of 15 MW can be expected from 100 m 3 bed volume. The reactor performance is limited by heat transfer.